Attitudes Towards Science During the Covid-19 Pandemic - Tobias Wingen; Oscar Lecuona; Simone Dohle (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
A better understanding of the public attitude towards science could be crucial to tackle the spread of mis- and disinformation related to the Covid-19 pandemic and beyond. We here contribute to this understanding by conceptualising and analysing the attitude toward science as a psychological network. For this analysis, we utilised cross-sectional data from a German probability sample (N = 1,009), the "Science Barometer", collected during the first wave of the Covid-19 pandemic. Overall, our network analysis revealed that especially the perceived value of science for curbing the pandemic is central to the attitude towards science. Beliefs about this value are related to trust in science and trust in scientific information and to positive and negative evaluations of scientific controversy and complexity. Further, valuing common sense over science was related to seeking less scientific information on official websites, suggesting that this belief, in particular, may drive mis- and disinformation and could be a promising target for interventions. Finally, we found no evidence that seeking scientific information on social media had detrimental consequences for the attitude towards science. Implications for health communication and science communication, limitations, and future directions are discussed.